Inadequacies of death certification in Beirut: who is responsible? - Sibai Abla M.; Nuwayhid Iman; Beydoun May; Chaaya Monique (The World Health Organization, 2002)
OBJECTIVE: To assess the completeness of data on death certificates over the past 25 years in Beirut, Lebanon, and to examine factors associated with the absence of certifiers' signatures and the non-reporting of the underlying cause of death. METHODS: A systematic 20% sample comprising 2607 death certificates covering the 1974, 1984, 1994, 1997 and 1998 registration periods was retrospectively reviewed for certification practices and missing data. FINDINGS: The information on the death certificates was almost complete in respect of all demographic characteristics of the deceased persons except for occupation and month of birth. Data relating to these variables were missing on approximately 95% and 78% of the certificates, respectively. Around half of the certificates did not carry a certifier's signature. Of those bearing such a signature, 21.6% lacked documentation of the underlying cause of death. The certifier's signature was more likely to be absent on: certificates corresponding to the younger and older age groups than on those of persons aged 15-44 years; those of females than on those of males; those of persons who had been living remotely from the registration governorate than on those of other deceased persons; and those for which there had been delays in registration exceeding six months than on certificates for which registration had been quicker. For certificates that carried the certifier's signature there was no evidence that any of the demographic characteristics of the deceased person was associated with decreased likelihood of reporting an underlying cause of death. CONCLUSION: The responsibility for failure to report causes of death in Beirut lies with families who lack an incentive to call for a physician and with certifying physicians who do not carry out this duty. The deficiencies in death certification are rectifiable. However, any changes should be sensitive to the constraints of the organizational and legal infrastructure governing death registration practices and the medical educational systems in the country.